No survival benefit associated with waiting for non‐lung donor heart transplants for adult recipients with congenital heart disease. Issue 5 (5th March 2021) - Diamant, Michael J.; Fox, Arieh L.; Modi, Vivek A.; Joshi, Aditya A.; Clark, Daniel E.; Bichell, David P.; Cedars, Ari; Fowler, Rachel; Frischhertz, Benjamin P.; Mazurek, Jeremy A.; Schlendorf, Kelly H.; Shah, Ashish S.; et al.
Abstract: Background: Adults with congenital heart disease (CHD) awaiting heart transplant (HT) have higher mortality and waitlist removal due to clinical deterioration than those without CHD. The selective use of non‐lung donors (NLD) to recover donor pulmonary vasculature to assist in graft implantation may be a contributing factor and is supported by consensus statements despite the recent use of pericardium or graft material as an alternative in pulmonary vascular reconstruction. The impact of selecting NLD for CHD recipients on wait time and mortality has not been evaluated. Methods/Results: In the United Network for Organ Sharing (UNOS) Registry, 1271 HT recipients age ≥ 18 with CHD were identified between 1987 and 2016, 68% of which had NLDs. Prior to HT, NLD recipients were significantly less likely to be listed UNOS Status 1A, require mechanical ventilation, or intra‐aortic balloon pump support. There was no difference in mean waitlist time (254 vs. 278 days, p  = .31), 1‐year mortality (82% vs. 80%, p  = .81; adjusted odds ratio 1.32, 95% confidence interval [CI] 0.96–1.83, p  = .08), or overall mortality (adjusted hazard ratio 1.08, 95% CI 0.86–1.36, p  = .48) between recipients from NLD and concomitant lung donors. Conclusions: Adult CHD patients who are less critically ill or listed at a lower status are more likely to receive HT from NLD. There is no overall mortality benefit associated with this practice. While specific cases may necessitate waiting for NLD, programs need to re‐evaluate whether this should remain a more widespread practice among CHD patients.